2022
DOI: 10.3390/app12073394
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive, Observer-Based Synchronization of Different Chaotic Systems

Abstract: In this study, the problem of master–slave synchronization of two different chaotic systems is considered and solved under a novel set of assumptions. The mathematical model of each of them contains unknown, constant parameters. Only a single output of the master system is available, and only a single input of the slave system is a control input. The proposed, novel approach is based on the active cooperation of the adaptive observer of the master system and adaptive controller of the slave. The tuning functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…At the beginning, the trajectories of bidimensional and three-dimensional attractor exhibit large open cycles that shrink until they become stabile closed cycles (Figures 10 12). The trajectories obtained in the GF model indicate the pure oscillatory behavior of B reaction (Figures 10-12), in which the amplitudes and frequencies of oscillations the de pend by time [32] and temperature [33]. For a high flow in the open reaction system, the concentrations of all intermediate species and parameter values listed in Table 2 presented oscillatory behaviors (Figures 6-8) in time (τ).…”
Section: High Flux Inputmentioning
confidence: 88%
See 1 more Smart Citation
“…At the beginning, the trajectories of bidimensional and three-dimensional attractor exhibit large open cycles that shrink until they become stabile closed cycles (Figures 10 12). The trajectories obtained in the GF model indicate the pure oscillatory behavior of B reaction (Figures 10-12), in which the amplitudes and frequencies of oscillations the de pend by time [32] and temperature [33]. For a high flow in the open reaction system, the concentrations of all intermediate species and parameter values listed in Table 2 presented oscillatory behaviors (Figures 6-8) in time (τ).…”
Section: High Flux Inputmentioning
confidence: 88%
“…At the beginning, the trajectories of bidimensional and three-dimensional attractors exhibit large open cycles that shrink until they become stabile closed cycles (Figures 10-12). The trajectories obtained in the GF model indicate the pure oscillatory behavior of BZ reaction (Figures 10-12), in which the amplitudes and frequencies of oscillations the depend by time [32] and temperature [33].…”
Section: High Flux Inputmentioning
confidence: 94%
“…In the past few decades, chaos synchronization has received great attention owing to its applications in designing secure communication systems. Various adaptive synchronization schemes have been developed in recent years such as sliding mode controller [60,61], backstepping neural network method [62,63], observer-based synchronization [64] and so on.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, an obvious technique to consider is to join an adaptive observer and an adaptive controller. This problem was investigated in [38] and it was observed that it requires the active cooperation of two adaptation mechanisms: the first acting in the observer and the other one in the controller. It is well known that adaptive observers for nonlinear systems require special conditions [39,40] and that the derivation of the stability and tuning is complicated.…”
Section: Introductionmentioning
confidence: 99%